In their words: How television and visual media can raise awareness of dementia and other health conditions that carry stigma, including disabilities. Issue 2 (1st October 2015) - Heward, Michelle; Palfreman-Kay, James; Innes, Anthea
This article explores the mutual contribution television and disability studies can make to one another, focusing on the role of television and visual media in raising awareness and challenging gaps in understanding of dementia, a health condition that carries stigma and is framed as a disability. The Living Well with Dementia Dorset Video (LWDDV) project demonstrates the duality of how creating and disseminating a video featuring people with dementia and carers talking about what it means to live well with the condition, provides a way to use media to raise awareness of dementia. Portraying real-life experiences of people affected by dementia was crucial, and enabled these often marginalized voices to be heard. Participants discussed experiences of diagnosis, post-diagnostic support, adjustments to lifestyle, social activities and family relationships. The video was disseminated through YouTube, and the impact on understandings of dementia was established through a questionnaire. Findings indicate personal stories are a powerful way to raise awareness of dementia, an approach that could improve awareness of other health conditions that carry stigma, including disabilities. Video provides researchers with novel ways to disseminate findings that extend to new and wide-ranging audiences.